Social Contracts and World Bank Country Engagements : Lessons from Emerging Practices - Independent Evaluation Group (World Bank, Washington, DC, 2019)
World Bank emphasizes the importance of social contracts to eliminate poverty and boost shared prosperity. In the 2014 World Bank Group Goals, the World Bank calls for social contracts that prioritize the poor while creating the conditions for equitable growth. This learning-oriented evaluation generates lessons from the World Bank’s experience using social contract diagnostics to help countries reshape their social contracts. It does this by:(i) evaluating the quality and value added of social contract diagnostics; (ii) assessing how social contract diagnostics are translated into operations; (iii) identifying the risks and challenges of integrating social contract diagnostics into operations; and (iv) drawing lessons on how to overcome these challenges. At the country level, this evaluation identified 21 Systematic Country Diagnostics (SCDs) that use a social contract framing to diagnose and explain complex development challenges such as entrenched inequalities, poor service delivery, weak institutions, and why decades of policy and institutional reforms promoted by external development actors could not fundamentally alter countries’ development paths.